Axial and appendicular postural abnormalities and associations with balance, gait and physical function in individuals with Parkinson's disease (Revista Contexto & Saúde, 2023)
Background: Individuals with Parkinson disease (PD) may have a flexed posture, but only axial postural abnormalities (PAs) are generally investigated. Purpose: The objective was to verify if PAs of the axial and appendicular skeleton observed in PD occur in an interrelated manner to maintain balance and physical function. Methods: A cross-sectional observational study. Sixty-nine individuals with PD were evaluated by computerized photogrammetry. The MDS-UPDRS scale was used to analyze the physical function and the Mini-BESTest to assess balance. To determine the relationship between PAs and clinical aspects, multiple linear regression analysis was performed, setting age and levodopa equivalent dose as covariates. Results: The anterior trunk inclination angles were significantly correlated with the flexion angles of the elbows, hips and knees (p˂0.01). Larger head flexion was correlated with worsening physical function (p=0.013) and gait (p=0.043); greater trunk, hip and knee flexion were correlated with reduced postural instability (p˂0.05), and greater knee flexion was correlated with improvements in gait deficits (p=0.013). Conclusion: Postural abnormalities in the axial and appendicular joints of people with PD appear to occur in an organized and interrelated manner as a body compensation used to improve physical function and reduce balance and gait deficits.
Keywords: doença de Parkinson; quilíbrio; fotogrametria; alterações motoras; postura